Biosorption of Heavy Metals from Acid Mine Drainages onto Pig Bristles, Poultry Feathers and Crustacean Shells Industrial Biowastes - Fernando I. Ramírez-Paredes; Teresa Manzano-Muñoz; Juan C. Garcia-Prieto; J. Felipe Bello-Estévez; Galina G. Zhadan; Valery L. Shnyrov; John F. Kennedy; Manuel G. Roig (Journal of Basic & Applied Sciences, 2013)
The removal of metals ions from aqueous solutions plays an important role in water pollution control. In this study, a biosorption process for the bioremediation of heavy metal-contaminated acid mine drainages, located in Western Spain, has been developed. The process is based on the physico-chemical properties for the adsorption, ion exchange, and complexation of metal ions by biopolymers keratin and chitin from different industrial biowastes such as pig bristles, poultry feathers and crustacean shells. The selectivity for metals, the first order kinetics and yields of the corresponding biosorption processes of uranium and other metals polluting such acid mine drainages by such biosorbents are described. The biowaste rich in keratin (pig bristles) seems to show a higher biosorption capacity than that of bioresidues rich in chitin (crustacean shells). Moreover, factors such as the lower contamination by metals of acid waters, the lower influent water volume/biosorbent mass ratio, the configuration of the packed-bed reactor and the partial hydrolysis of keratin increase both the capacity and the rate of the process of metal biosorption onto the biosorbent.